Functional Characterization of Invertase Inhibitors PtC/VIF1 and 2 Revealed Their Involvements in the Defense Response to Fungal Pathogen in Populus trichocarpa - Su, Tao; Han, Mei; Min, Jie; Zhou, Huaiye; Zhang, Qi; Zhao, Jingyi; Fang, Yanming (Frontiers in Plant Science, 2020)
In higher plants, cell wall invertase (CWI) and vacuolar invertase (VI) were considered to be essential coordinators in carbohydrate partitioning, sink strength determination, and stress responses. An increasing body of evidence revealed that the tight regulation of CWI and VI substantially depends on the post-translational mechanisms, which were mediated by small proteinaceous inhibitors (C/VIFs, Inhibitor of β-Fructosidases). As yet, the extensive survey of the molecular basis and biochemical property of C/VIFs remains largely unknown in black cottonwood (Populus trichocarpa Torr. & A. Gray), a model species of woody plants. In the present work, we have initiated a systematic review of the genomic structures, phylogenies, cis-regulatory elements, and conserved motifs as well as the tissue-specific expression, resulting in the identification of 39 genes encoding C/VIF in poplar genome. We characterized two putative invertase inhibitors PtC/VIF1 and 2, showing predominant transcript levels in the roots and highly divergent responses to the selected stress cues including fusarium wilt, drought, ABA, wound, and senescence. In silico prediction of the signal peptide hinted us that they both likely had the apoplastic targets. Based on the experimental visualization via the transient and stable transformation assays, we confirmed that PtC/VIF1 and 2 indeed secreted to the extracellular compartments. Further validation of their recombinant enzymes revealed that they displayed the potent inhibitory affinities on the extracted CWI, supporting the patterns that act as the typical apoplastic invertase inhibitors. To our knowledge, it is the first report on molecular characterization of the functional C/VIF proteins in poplar. Our results indicate that PtC/VIF1 and 2 may exert essential roles in defense- and stress-related responses. Moreover, novel findings of the up- and downregulated C/VIF genes and functional enzyme activities enable us to further unravel the molecular mechanisms in the promotion of woody plant performance and adapted-biotic stress, underlying the homeostatic control of sugar in the apoplast.